Islamic civilization: factors behind its glory and decline - Ashimi, Tijani Ahmad (International Journal of Business, Economics and Law (IJBEL), 2016)
Civilization is widespread of quality civic idea, supported by full development of arts, maintained with enthusiasm to pursuit the knowledge in which many ethnicities and religions may participate. It begins from the time of the settlement of the first man on this earth. Almost every nation has contributed to the history of civilization, although the contribution may vary from one nation to another. What may distinguish one civilization from one another is the strength of the foundation on which these civilizations have been founded and the impact these civilizations have made to humanity as a whole. Based on this fact, Islamic Civilization which may be synonymous to tawhidic civilization is based on a unity of God which stands completely against any racial or ethnic discrimination. Such major racial and ethnic groups as the Arabs, Persians, Turks, Africans, Indians, Chinese and Malays in addition to numerous smaller units embraced Islam and contributed to the building of Islamic civilization. Moreover, Islam was not opposed to learning from the earlier civilizations and incorporating their science, learning, and culture into its own world view, as long as they did not oppose the principles of Islam. Indeed, historically speaking, during the period when Western civilization was experiencing the dark ages, between 700-1200 A.D, Islamic empire stretched from Central Asia to southern Europe. Scholarly learning was highly prized by Arab Muslims and the people, and they contributed greatly to science and mathematics. Many classical Greek and Roman works were translated into Arabic, and scientists expanded on the ideas. Yet, in this modern era, many seem to jubilate our past glory, without paying enough attention to the cause and impetus that contributed to that glory of Islamic civilization, and others tend to marginalize (if not ignore) the factors behind its collapse and decline. Therefore, this article by applying historical approach will explore the factors and raison d’etre of rise and fall of Islamic Civilization. And lastly, the article will provide some solutions and lessons that can be learned from rise and fall of Islamic civilization.